Vocabulary retention, sustained attention, and enjoyment: Using Tick8 method to promote language achievement - Safoura Jahedizadeh; Abbas Khademorreza; Somaye Sarvari (Australian Journal of Applied Linguistics)
Although language skills have gained unparalleled momentum in language education, there is a paucity of research on one of the most significant subskills, vocabulary. Due to the underestimation of an efficient method to learn foreign language vocabularies, scant research attention has been dedicated to exploring the best vocabulary learning method. The major aim of this mixed-methods research is to assess the effectiveness of a departed vocabulary learning method, Tick8, on students’ vocabulary knowledge. It also delves into exploring its impact on learners’ sustained attention and enjoyment. Via an experimental design, 62 female middle school students were randomly assigned to control (N=31) and experimental (N=31) groups. The results of the study evidenced the positive role of Tick-8 technique in participants’ vocabulary learning and retention. The results of the semi- structured interviews with a number of participants also strengthened the results of the quantitative phase. Moreover, the results indicated significant differences between the control and experimental groups regarding their enjoyment, however the results of sustained attention were not significant. In other words, Tick-8 Technique positively influenced student's enjoyment, but did not affect students’ sustained attention.